First Results on Lake Bathymetry of Panch-Pokhari Complex, Langtang Region, Central Nepal (Journal of Tourism and Himalayan Adventures, 2024)
The Panch-Pokhari complex, a group of five lakes, is one of the high-altitude wetlands of Nepal that has received very less attention. While these lakes hold significant religious importance, they are less known from a morpho-ecological perspective. The objective of this study is to develop a bathymetry model of the lakes through afield survey and geospatial analysis. This study generated new insights into the limnological and morphometric features of the five lakes through detailed mapping and profiling. The bathymetric analyses revealed diverse basin morphometry among the lakes, with Lake 1 being the largest, in term of its depth of 12.1 m and water volume of 208,352 m3. In contrast, Lake 5 was the smallest and the shallowest with a depth of 1.4 m and volume of 1,921 m3. This study establishes a new baseline to advance scientific understanding of the Panch-Pokhari complex. Further, integrated research combining limnological, ecological, and social aspects is recommended to support evidence-based planning for the conservation of these vital Himalayan wetlands.